Characterization of extracellular cytotoxic protein of Vibrio spp.isolated from freshwater carps and prawns - Pushpita, Mishra; Samanta, Mrinal; Maiti, Nikhil Kumar; Sarangi, Niranjan (Indian Journal of Fisheries, 2016)
Several Vibrio species which are part of the microflora in the coastal, brackish and freshwater environments cause vibriosisin economically important fishes. In this study, Vibrio parahaemolyticus, Vibrio harveyi and Vibrio fluvialis were isolatedfrom the gastrointestinal tract of Labeo rohita, Catla catla, Cirrhinus mrigala and also from Macrobrachium rosenbergii andMacrobrachium malcolmsonii. The extracellular products of these bacteriaÂ produced cytopathic effect in MDBK cell butthey did not damage DNA of MDBK cells as detectedÂ by RAPD-PCR. A 43 KD protein was precipitated from the extracellular products with 70% ammonium sulphate saturation which was found to be antigenic by immunobloting.